2020
DOI: 10.3390/ani10050838
|View full text |Cite
|
Sign up to set email alerts
|

Dogs and Cats: Reservoirs for Highly Diverse Campylobacter jejuni and a Potential Source of Human Exposure

Abstract: Assessing the carriage of Campylobacter in animal reservoirs is essential to better understand Campylobacter epidemiology. Here, we evaluated the prevalence of thermophilic Campylobacter spp. in dogs and cats, hereafter defined as pets, and characterized Campylobacter jejuni (C. jejuni) isolates to assess their genetic diversity and their potential link with isolates from other animals or human cases. During a 6-month period, 304 feces samples were collected from pets. A significantly higher prevalence of ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 41 publications
6
24
1
Order By: Relevance
“…C. jejuni has been reported as the most predominant species, whereas C. coli showed mostly lower rates. Compared with our results, Thèpault et al [ 54 ] and Karama et al [ 55 ] reported a higher prevalence of C. jejuni (24.4% and 29.1%, respectively), but lower values regarding C. coli (2.6% and 5.4%, respectively). In Slovakia, Badlìk et al [ 56 ] isolated C. jejuni and C. coli with a prevalence of 51.2% and 9.8%, respectively.…”
Section: Discussioncontrasting
confidence: 82%
“…C. jejuni has been reported as the most predominant species, whereas C. coli showed mostly lower rates. Compared with our results, Thèpault et al [ 54 ] and Karama et al [ 55 ] reported a higher prevalence of C. jejuni (24.4% and 29.1%, respectively), but lower values regarding C. coli (2.6% and 5.4%, respectively). In Slovakia, Badlìk et al [ 56 ] isolated C. jejuni and C. coli with a prevalence of 51.2% and 9.8%, respectively.…”
Section: Discussioncontrasting
confidence: 82%
“…Further, C. jejuni is associated with several sequelae including reactive arthritis, Guillain-Barre syndrome, Miller-Fisher syndrome and prolonged exposure in infants is associated with growth deficits [7][8][9]. Although considered a foodborne pathogen in humans, C. jejuni can be acquired from a wide range of sources including retail meats, raw milk, companion animals, fecal contamination, wild birds and other environmental reservoirs [10,11]. C. jejuni is also increasingly viewed as a reservoir for antibiotic resistance genes in both the environment and the food supply chain [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that puppies had a high prevalence in comparison with the adult dogs (Parsons et al 2010;Leonard et al 2011;Rahimi et al 2012;Kumar et al 2012;Holmberg et al 2015;Selwet et al 2015;Thépault et al 2020), this may be an indication that they lack prior exposure to the immune system. There is no proof of any sex or animal breed predispositions in the literature published so far.…”
Section: Factors Associated With Campylobacter Spp Prevalence In Dogs Signalmentmentioning
confidence: 99%